2015
DOI: 10.12816/0017352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Capital Structure on Corporate Performance : A Pre and Post Crisis Evaluation of Selected Companies in US

Abstract: Capital structure relationship with corporate performance as an unresolved issue became more complicated after the global crisis. This is because of liquidity problems that ensued and firms were looking for strategies of cost reduction and profit increment with a view to enhance performance. This paper examines the impact of capital structure choices (Equity or Debt) on performance of selected firms in US in the pre, during and post crisis periods (2003-2006), 2007-2008 and 2009-2012 respectively) with a view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Agency theory is concerned with resolving the conflicts of interest between managers and shareholders. This conflict may involve managers to favour accomplishing their personal goals as a substitute of maximizing the company's value and shareholders' returns (Jensen and Meckling, 1976) as cited in Olaniyi et al (2015). In addition, increasing the voluntary disclosure can reduce the agency and monitoring costs as a result of conflicts of interest (Marston and Polei, 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Agency theory is concerned with resolving the conflicts of interest between managers and shareholders. This conflict may involve managers to favour accomplishing their personal goals as a substitute of maximizing the company's value and shareholders' returns (Jensen and Meckling, 1976) as cited in Olaniyi et al (2015). In addition, increasing the voluntary disclosure can reduce the agency and monitoring costs as a result of conflicts of interest (Marston and Polei, 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As reflected in relevant and related financial ratios, theoretical findings have emphasized the positive influence of debt on profitability and expected deterioration of liquidity position (Modigliani and Miller, 1963;Jensen and Meckling, 1976;Myers, 1984, Myers andMajluf, 1984). However, other empirical evidence have shown mixed results (Abor, 2005;Sarlija and Harc, 2012;Olaniyi et al 2015;Foyeke et al 2016;Vo and Ellis, 2017). Booth et al (2001) concluded that the capital structure of companies affects their performance equally across the developed and developing economies.…”
Section: Theory and Review Of Literaturementioning
confidence: 99%
“…Extant literature has focused on the determinants of capital structure (Lipson and Mortal, 2009;Anderson and Carverhill, 2010;Udomsirikul et al 2010;Akinyomi and Olagunju, 2013;Anthony and Odunayo, 2015;Sharma and Paul, 2015;Ghasemi and Ab-Razak, 2016), and the impact of capital structure on profitability/ performance and possibly liquidity as a control variable (Rajan and Zingales, 1995;Uremadu, 2012;Ebimobowei et al 2013;Olaniyi et al 2015;Akhtar et al 2016;Dahiru et al 2016;Foyeke et al 2016;Vy and Nguyet, 2017). Meanwhile, the trade-off between debt and equity component of capital structure does significantly impact on the trade-off between profitability and the risk of bankruptcy associated with liquidity (Rajan and Zingales, 1995;Anderson and Carverhill 2010;Burksaitiene and Draugele, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini disebabkan oleh perusahaan yang menggunakan hutang secara strategis untuk menunjukkan bahwa perusahaan dapat mempengaruhi posisi kompetitifnya. Olaniyi et al (2015) menjelaskan bahwa struktur modal merupakan cara berbeda yang tersedia bagi perusahaan untuk membiayai kegiatan operasionalnya. Sebuah perusahaan dapat membiayai bisnisnya hanya dengan ekuitas, hanya hutang atau kombinasi dari keduanya.…”
Section: Tabel 3 Uji Tunclassified